Magnetic Resonance Imaging of Arteriovenous Malformation of Pinna: A Case Report (TAJ: Journal of Teachers Association, 2022)
Vascular malformations and tumors comprise a wide, heterogeneous spectrum of lesions that often present a diagnostic and therapeutic challenge. Auricular AVM is a rare entity & needs MRI & MR angiography for optimal diagnosis and proper pre & post-operative evaluation and management. Very few such cases were reported in previous literatures. We present a rare case of auricular AVM in a 20 year old woman. MRI with MRA showed the lesion extension & characteristics excellently & also depicted the posterior auricular & superficial temporal arteries to be the feeding vessels. Clinical suspicion of AVM was confirmed by imaging & the patient was referred for surgical excision.TAJ 2021; 34: No-2: 129-133